Challenges and opportunities for food processing to promote consumption of pulses - Pinto, Alexandra (2019)
The benefits that pulses bring to the consumers - nutritional, health and environmental - meet several of the current consumption trends in the EU. The evolution of pulses consumption in the European regions displays two different panoramas: the North-South disparity and the similar lower consumption in the Eastern and Western regions. To improve consumer acceptance it is crucial to invest on educating and communicating to the consumers how pulses can contribute to healthy and sustainable diets. Here we present different food processing technologies that have the potential to increase not only the nutritional and organoleptic quality of pulses, but also it´s convenience of use as this emerges as a growing factor in the decision to purchase and food choice of consumers. This approach also includes the culinary innovation for the development of appealing, convenient and nutritive meals with healthy and environmental claims.